2014
DOI: 10.1038/bmt.2014.179
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality following hematopoietic stem cell transplantation: longitudinal trajectories and biobehavioral correlates

Abstract: The present study examined changes in sleep quality following hematopoietic stem cell transplantation (HSCT) and investigated associations with biobehavioral factors. Individuals undergoing HSCT for hematologic malignancies (N = 228) completed measures of sleep quality and psychological symptoms pre-transplant and 1, 3, 6 and 12 months post transplant. Circulating inflammatory cytokines (IL-6, TNF-α) were also assessed. Sleep quality was poorest at 1 month post transplant, improving and remaining relatively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 41 publications
8
51
0
Order By: Relevance
“…Moreover, a higher initial level of physical symptoms was also related to higher pre-HSCT depressive symptoms. Positive relationships between these variables were observed in previous studies [ 13 , 27 , 28 ]. One explanation for this effect is that depression is associated with increased adverse symptom burden [ 40 ] via pathophysiologic processes (e.g., increased cytokine level or other inflammatory factors) [ 41 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, a higher initial level of physical symptoms was also related to higher pre-HSCT depressive symptoms. Positive relationships between these variables were observed in previous studies [ 13 , 27 , 28 ]. One explanation for this effect is that depression is associated with increased adverse symptom burden [ 40 ] via pathophysiologic processes (e.g., increased cytokine level or other inflammatory factors) [ 41 ].…”
Section: Discussionsupporting
confidence: 75%
“…Adverse physical symptoms are common indicators of the health-related quality of life (HRQOL) physical domain [ 12 ]. Earlier studies suggest that poorer physical condition is associated with diminished well-being of patients [ 13 ], a lower psychological domain of HRQOL [ 14 ], higher distress, anxiety and depression [ 13 , 15 18 ], and poorer health prognosis and survival rates [ 19 21 ]. Physical functioning of patients after HSCT is frequently the focus of studies.…”
Section: Introductionmentioning
confidence: 99%
“…53 Other investigators have also identified reciprocal relationships among mood disturbance, sleep and fatigue in allogeneic HCT survivors. 54,55 Although parsing fatigue from depression is challenging, 56 the use of single item measures of anxiety, depression and sleep may have reduced our power to identify associations among these symptoms. Additional exploration of the relationships between fatigue and disturbances in sleep and mood in transplant survivors with cGvHD appears warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization for cancer treatment disrupts children's sleep pattern through changes in routines, environmental light and noise, pain, chemotherapy side effects, and awakenings for care provision . High‐dose chemotherapy (HDCT)/stem cell transplantation appear to confer particularly severe sleep problems, in the short‐term during transplant and over the longer‐term in survivors …”
Section: Introductionmentioning
confidence: 99%
“…severe sleep problems, in the short-term during transplant and over the longer-term in survivors. [10][11][12] Sleep disturbances are associated with significant long-term morbidities. Short duration and poor quality sleep are associated with suboptimal neurodevelopmental outcomes in healthy children, 13,14 and with development of cardiovascular and metabolic disease and obesity.…”
mentioning
confidence: 99%